Comparison of transoral endoscopic thyroidectomy vestibular approach and open conventional thyroidectomy regardıng inflammatory responses, pain, and patient satisfaction: a prospective study - Ünlü, Mehmet Taner; Aygun, Nurcihan; Serin, Erdinc; Uludag, Mehmet (Frontiers in Surgery, 2023)
Introduction The application of transoral endoscopic thyroidectomy vestibular approach (TOETVA) is becoming widespread throughout the world. We primarily aimed to evaluate the severity of surgical trauma in TOETVA and conventional open thyroidectomy (COT) regarding the inflammatory response including the comparison of surgical stress markers [interleukin-6 (IL-6), C-reactive protein (CRP), white blood cell (WBC)]. Material and method This non-randomized prospective study enrolled two groups with 20 patients each: COT group and TOETVA group. Patients aged 18–65 years with benign thyroid disease; with fine needle aspiration biopsy results of Bethesda III, IV or Bethesda V, VI (<1 cm nodule); thyroid volume <50 cm3; nodule diameter <4 cm; female gender without a previous neck, chin, and/or oral surgery; without vocal cord paralysis preoperatively; and patients in euthyroid state were enrolled to the study. Preoperative, postoperative second hour, first day, and second day CRP, WBC, and IL-6 levels were evaluated. Pain intensity was evaluated with the visual analog scale (VAS) score on the 2nd and 12th hour, 1st and 2nd days postoperatively. Results All the patients were female and mean age was significantly higher in the COT group. The operative time was significantly longer in the TOETVA group. No significant difference was found between the two groups regarding IL-6 levels. In the TOETVA group, postoperative second hour WBC value (p = 0.044) and first (p = 0.002) and second day (p = 0.005) CRP values were significantly higher. In the TOETVA group, the lower lip and lower chin VAS scores were significantly higher at 2nd and 12th hour, on the first and second days. The anterior neck VAS score was significantly higher in the TOETVA group at the second hour (p = 0.025). General and cosmetic satisfactions were similar at the 15th and 30th days in both groups. Conclusion The longer operative time and higher postoperative CRP level and VAS score in the chin and lower lip in the TOETVA group suggested that the method is not a minimally invasive technique compared to COT. However, the presence of similar total complication rates and early postoperative general and esthetic satisfaction that improves over time in both groups suggests that the clinical effect of increased magnitude of systemic inflammatory response in TOETVA might be temporary and acceptable.